PENGARUH SALES GROWTH, OPERATING CAPACITY, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Cindy Kwok; Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to obtain empirical evidence about the effect of sales growth, operating capacity, and leverage on financial distress in manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2020 period. The sample selection technique used purposive sampling method with the number of samples obtained were 71 companies and 213 data. The data processing technique uses multiple linier regression analysis with the help of the EViews 12 software program. The results of this study indicate that sales growth has no effect on financial distress, operating capacity has a positive and significant effect on financial distress, while leverage has a negative and significant effect on financial distress.